Chemical Versus Mechanical Denudation in Meta‐Clastic and Carbonate Bedrock Catchments on Crete, Greece, and Mechanisms for Steep and High Carbonate Topography. Issue 12 (17th December 2019) - Ott, Richard F.; Gallen, Sean F.; Caves Rugenstein, Jeremy K.; Ivy‐Ochs, Susan; Helman, David; Fassoulas, Charalampos; Vockenhuber, Christof; Christl, Marcus; Willett, Sean D.
Abstract: On Crete—as is common elsewhere in the Mediterranean—carbonate massifs form high mountain ranges whereas topography is lower in areas with meta‐clastic rocks. This observation suggests that differences in denudational processes between carbonate‐rich rocks and quartzofeldspathic units impart a fundamental control on landscape evolution. Here we present new cosmogenic basin‐average denudation rate measurements from both 10 Be and 36 Cl in meta‐clastic and carbonate bedrock catchments, respectively, to assess relationships between denudation rates, processes, and topographic form. We compare total denudation rates to dissolution rates calculated from 49 new and previously published water samples. Basin‐average denudation rates of meta‐clastic and carbonate catchments are similar, with mean values of 0.10 mm/a and 0.13 mm/a, respectively. The contribution of dissolution to total denudation rate was <10% in the one measured meta‐clastic catchment, and 40% for carbonate catchments ( 0.05 mm/a), suggesting the dominance of physical over chemical weathering at the catchment scale in both rock types. Water mass‐balance calculations for three carbonate catchments suggests 40–90% of surface runoff is lost to groundwater. To explore the impact of dissolution and infiltration to groundwater on relief, we develop a numerical model for carbonate denudation. We find that dissolution modifies the river profile channel steepness, and infiltration changes the fluvial response time to external forcing. Furthermore, we show that infiltration of surface runoff to groundwater in karst regions is an efficient way to steepen topography and generate the dramatic relief in carbonates observed throughout Crete and the Mediterranean. Key Points: Quantifying chemical and mechanical denudation in meta‐clastic and carbonate bedrock Dominance of mechanical denudation in karstic terrains Dissolution and infiltration in carbonate terrains influence the shape and response of river profiles to external forcing